OCORRÊNCIA E DISTRIBUIÇÃO DE IRIDACEAE NO ESTADO DO PARANÁ E ANATOMIA FLORAL EM ESPÉCIES DA TRIBO TIGRIDIEAE - KRÜGER, LARISSA DAL MOLIN (2016)
Iridaceae is a family with worldwide distribution, and wild distribution in Brazil. The tribe Sisyrinchieae, Trimezieae and Tigridieae belong to Iridoeae subfamily. The family is characteristic for present nectar and/or pollen oil as floral reward. In addition, Iridaceae has compounds of secondary metabolism stored in specialized cells (idioblasts) that give the family reproductive and defense strategies. The aims of the current study was to survey the Iridaceae occurrence of Paraná and where this occurs in the natural area, besides being accomplished floral anatomy of four species of the tribe Tigridieae such as Phalocallis coelestis, Calydorea coelestis, Cypella sp. and Herberbia lahue . The family of occurrence for the state of Paraná occurred through herbal review, and studies published. To survey the species in natural areas, it was conducted in 10 sampling points collected. The anatomical studies of the species were made through already established samples submitted amid include using plastic resin to anatomy. The result of this study revealed the occurrence of 72 species for the state through the survey in herbarium and literature. In the field areas were sampled Sisyrinchium micranthum, S. nidulare, S. alatum, S. palmifolium, S. luzula, S. hasslerianum, S. setaceum, S. restioides, S. weirii, S. Brasilia, S. sellowiannun, S. plicatulum, S. commutatum, Phalocallis coelestis, Herbertia lahue and Calydorea basaltica. Regarding the floral anatomy, the four backlight species studied showed anatomical differences, and also for the deposition of phenolic compounds in specialized cells called idioblasts. Idioblasts containing phenolic compounds were found in all C. basaltica structures in the nucellus of Cypella sp and ovarian Herbertia lahue. Calcium oxalate was the C. basaltica. ovaries and H.lahue. Starch was associated mainly in the area of vascular bundles in P. coelestis, Calydorea basaltica and Cypella sp. This study confirms that Iridaceae has great natural occurrence in Paraná, and the field areas it was reported a new record for the state. The anatomy of the tribe Tigridieae revealed the presence of trichomes secreting flowers that may be related to the attraction of pollinators and floral visitors.